Giant Mesenteric Cyst and Right Sided Syndrome in a 15-Year-Old Boy - Tamene, Ayanaw; Desta, Melkam; Tebeje, Habeneyom; Getie, Yeshiambel; Berhane, Hailemariam (European Journal of Pediatric Surgery Reports, 2019)
Giant mesenteric cyst is a rare benign abdominal tumor. It usually arises from the mesenteric side of the small bowel. Right side syndrome is the term used for congenital absence of right kidney and right testis. We report on a 15-year-old male who presented with progressive abdominal distension, early satiety, and difficulty walking or running. Abdominal ultrasound and computed tomography (CT) revealed a giant mesenteric cyst, absence of the right kidney, and left moderate hydronephrosis. After excision of the cyst, the patient was fully recovered. Our report shows that both conditions may occur in the same patient and therefore an association of these two diseases cannot be excluded.
Keywords: cryptorchidism; giant mesenteric cyst; renal agenesis; right side syndrome